The effects of land management (grazing intensity) vs. the effects of topography, soil properties, vegetation type, and climate on soil carbon concentration in Southern Patagonia - Peri, Pablo Luis; Ladd, Brenton; Lasagno, Romina Gisele; Martínez Pastur, Guillermo José (Elsevier, 2018)
Grazing is an economically important activity in Southern Patagonia’s steppe and woodland ecosystems. In the past, emphasis has been on maximizing the provisioning capacity of these ecosystems with little concern for the longer term conservation of the ecosystem services related to climate regulation, like carbon sequestration. This is changing rapidly as livestock producers in the region work to develop a certification scheme for sustainable land management for Patagonians rangelands. This study is a scientific contribution towards this broader social objective in which we test whether soil C concentration in topsoil (10 cm depth) can be used as an indicator of rangeland condition. Data on climate, soil chemistry, topography, ecosystem type and stocking rates were obtained from the PEBANPA network of permanent plots database for 145 sites across Southern Patagonia. These variables were used as independent variables in a partial least squares regression in which top soil C was the dependent variable. The effects of land use (stocking rate) on top soil C were barely detectable at the regional scale in Patagonia. Top soil C was however strongly associated with other independent variables, notably soil chemistry and climate variables and also vegetation type. Thus, changes in land use management may not have a significant impact on soil carbon sequestration in these types of ecosystems. This may be because many factors interact to determine top soil C such that the footprint of overgrazing on top soil C is drowned out at the regional scale by other variables. This highlights the need for further work to develop indicators for sustainable land management in the region.